Direct Costs of Care for Adolescent Patients with and Without Persisting Concussion Symptoms in United States Secondary Schools: A Report from the Athletic Training Practice-Based Research Network. Issue 5 (31st May 2022) - Weber Rawlins, Michelle L.; Marshall, Ashley N.; Lam, Kenneth C.; Valovich McLeod, Tamara C.
Background: Concussions present significant public health concerns and associated medical costs, especially for those with persisting concussion symptoms. Purpose: To compare direct costs of care for adolescent patients managed within the secondary school setting with and without persisting concussion symptoms. Methods: Our study was a retrospective analysis of medical records using the Athletic Training Practice-Based Research Network which included records from 59 secondary schools in the United States. Participants included 282 adolescent patients following a concussion (male=199, female=83, age=15.5 years, 95% CI:15.3, 15.6). Complete patient cases were identified using International Classification of Diseases and Related Health Problems diagnostic codes for concussion between 2010-2017. We calculated summary statistics for common services and direct costs of care, calculated based on reimbursement rates for Current Procedural Terminology codes. Patients were grouped as with (symptoms experienced 28 days; n=38) and without (symptoms experienced <28 days; n=238) persisting concussion-related symptoms. A Mann-Whitney U test was used to determine if direct cost of care differed between groups (n=276, α=0.05). We used a linear regression to determine cost for each additional day of care. Results: The most common service was an athletic trainer re-evaluation (n=1012/1560, 64.9%). The average total direct costs of care was US $286.30 per adolescent patient (95% CI: US $260.14-312.45). Significantly higher direct costs of care were reported for patients with persisting symptoms ( p <0.001; persisting: median=US $471.07, IQR=US $281.21-564.93, 95% CI: US $367.05-528.11; without persisting: median=US $210.95; IQR=US $117.45-337.52, 95% CI: US $234.28-286.82). The concussion base price was US $174.42 (95%CI: US $129.75-219.10) and each additional day cost US $5.99 (95% CI: $3.99-7.99). Conclusions: Our findings provide insight to potential costs associated with adolescent patients who are managed within the secondary school setting following a concussion. These results highlight the potential economic value of sports medicine professionals within the school setting. Other health care professionals not in the school setting may advise patients to first be evaluated and managed by the site athletic trainer if able and in accordance with state law, prior to an office visit to also reduce care costs as many athletic trainers do not charge for their services. Future research should examine how to decrease the economic burden for patients.